The struggle for national education (Chapman and Hall, 1873)
Facsimile reprint: [Brighton], The Harvester Press, 1972. Ed. with an introd. by A. Briggs. 61 p. (Society & the Victorians. General editors: J. Spiers and C. Ballantine). PAMPHLET VOLUME.